Improving Observing and Communicating Skills Through the Implementation of Problem Based Instruction on Learning Biology in Senior High School - Ramadhan, Mutiara (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The purpose of this research is to improve observing and communicating skills of student on learning biology. The research was a Classroom Action Reasearch (CAR) that has been done in two cycles and each cycle consists of plan, action, observation, and reflection. The subjects of this research are 36 students of X grade. Data are obtained by observation, test, interview, and documentation. The analysis of this data use quantitative descriptive technique. The validity of data use technique of triangulation. The target of this research is to increase percentage of observing and communicating skills about â‰¥ 30% does archieved. The improvement of observing skill can be showed by increasing the average percentage that reached by student from 50,79% in pre-cycle to 66,11% in cycle I, and increase to 81, 97% in cycle II. The improvement of communicating skill can be showed by increasing the average percentage that reached by student from 40,19% in pre-cycle to 54,75% in cycle I, and increase to 77,99% in cycle II. Based on the result above the conclusion of this research is thereâ€™s an improvement of observing and communicating skills of student using problem based instruction